Cancer pain and related symptoms: an overview - Paice, Judith (Henry Stewart Talks, 2009)
Scope of the problem, Consequences of unrelieved cancer pain, Prevalence of cancer pain, Common cancer pain syndromes, Special populations, Barriers to cancer pain relief, Who develops chronic cancer pain
Archived at 2021/07/29